Serum gentamicin assay: A comparison and assessment of different methods. Issue 6 (June 1974) - Phillips, I.; Warren, Christine; Smith, S. E.
Abstract : We have compared, in a clinical laboratory, three methods for estimating the concentration of gentamicin in serum. The adenylase method is most accurate, but requires considerable skilled technical time and expensive apparatus. The urease method requires an accurate pH meter but is otherwise inexpensive, but in our hands, although it produces results most rapidly, it also requires considerable technician time and is least accurate. The agar diffusion method requires no expensive apparatus, least technician time, and produces results of acceptable accuracy. It does, however, take longer than the other two methods to produce results.